2010
DOI: 10.1889/1.3499894
|View full text |Cite
|
Sign up to set email alerts
|

10.2: Crosstalk Suppression by Image Processing in 3D Display

Abstract: We proposed a Digital Crosstalk Reduction (DCR) method to suppress optical crosstalk in 3D display without using any extra hardware components. Furthermore, DCR method can be applied to most of the 3D display technologies. In this paper, a 17-inch pattern retarder stereoscopic display and a 12-views autostereoscopic display were verified to yield less crosstalk by applying DCR method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Then node Q1 of SRB is pre-charged to VGL and T2 is turned on. Because SCLK3, which is applied to the CLK2 terminal of first stage, is still at VGH, OUT [1] is also at VGH. In this condition, when SCLK3 goes low to VGL, V Q1 of SRB goes lower than VGL by the bootstrapping through capacitor C1.…”
Section: Proposed Pmos Gate Drivermentioning
confidence: 99%
See 1 more Smart Citation
“…Then node Q1 of SRB is pre-charged to VGL and T2 is turned on. Because SCLK3, which is applied to the CLK2 terminal of first stage, is still at VGH, OUT [1] is also at VGH. In this condition, when SCLK3 goes low to VGL, V Q1 of SRB goes lower than VGL by the bootstrapping through capacitor C1.…”
Section: Proposed Pmos Gate Drivermentioning
confidence: 99%
“…For flat panel displays such as AMOLEDs and LCDs, stereoscopic and auto-stereoscopic methods have both been applied to achieve left-right image separation. However, an undesirable effect, crosstalk, can occur while separating the left and right eye images sequentially or spatially [1,2]. When the crosstalk phenomenon occurs, image content intended for the left eye is shown to the right eye, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…For a system designer, it is found that the maximum tolerable system crosstalk using subjective evaluation is about 20% with a mirror-type 3D display. Chang et al [5] studied the crosstalk that affects the quality of stereoscopic 3D moving images with different Z-directional speeds. For time-sequential stereoscopic displays with active shutter glasses, which show the left and right eye image flipping in time by alternately switching on and off each glass, the shutter glass for left eye is completely transparent when the left-eye image is displayed on the screen in ideal case, while the shutter glass for right eye completely blocks the light.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional approaches to crosstalk reduction mainly focus on how to drive backlight or glasses. For example, backlight blinking [2] and shortening the period of opening glass shutter [3] are well known methods. However, their drawbacks are that they decrease brightness or cause flicker.…”
Section: Introductionmentioning
confidence: 99%